Price Dynamics and Demand Elasticity in the Platform Economy Era: A Quantitative Analysis of the Online Retail Sector in Indonesia - Husin Lubis, Ahmad (International Journal of Economics (IJEC), 2026)
This study investigates the determinants of price dynamics and demand elasticity in Indonesia's online retail sector, with particular emphasis on platform economy effects during the 2024-2025 period. Employing a double-log regression methodology with ordinary least squares (OLS) estimation, we analyze transaction-level data from major e-commerce platforms including Shopee, Tokopedia, and Lazada. The research reveals that demand elasticity in the Indonesian online retail market exhibits pronounced price sensitivity (elasticity coefficient: -1.23 to -1.67), indicating elastic demand characteristics. Cross-price elasticity estimates suggest significant substitution effects between platforms (range: 0.45 to 0.78), driven by the mobile-first architecture and promotional intensity of the digital ecosystem. Dynamic pricing mechanisms implemented by major platforms demonstrate adaptation to localized demand variations and competitive pressures. Our findings demonstrate that platform-based price competition generates downward pressure on margins while increasing consumer surplus, with elasticity heterogeneity across product categories ranging from -0.89 (electronics) to -1.95 (fashion and accessories). The study provides quantitative evidence that platform economy dynamics fundamentally reshape traditional price-demand relationships in emerging markets, offering actionable insights for retailers, policymakers, and platform operators managing competitive pricing strategies in this rapidly evolving ecosystem